BUSINESS MODELS AND COMPETITIVE ADVANTAGE: A DYNAMIC APPROACH - Soraya Cardoso Pongelupe Lopes (Revista Ibero Americana de Estratégia, 2019)
Objective: Demonstrate how the Canvas business model can become dynamic from a conceptual perspective. Methodology/approach: This study is qualitative, descriptive and exploratory, with a theoretical approach, based on the foremost theorists. Originality /Relevance: This study presupposes the importance of strengthening the business model literature on the competitive dynamic perspective. It defines the assumptions of a DMB and differentiates it from a static model. That enables the evaluation of the factors that cause a BMC to become static and thus not equipped to allow a business logic that creates value and generates a competitive advantage. Main results: At the end of the present essay, it is possible to understand, from a theoretical perspective, how the DBM contributes to value creation and the generation of sustainable advantage in high-change environments. Theoretical/methodological contributions: The present study has identified three conceptual assumptions that constitute the DBM. First, there is the design of the business models – interdependence and connection between their constitutive elements. Second, the business models linked to dynamic capabilities. Finally, the search for the capture of value and generation of sustainable competitive advantages by the companies. By those assumptions, it was possible to introduce a conceptual model for DBM and BMC evaluation from the perspective of a dynamic model.